Effects of rosiglitazone on serum paraoxonase activity and metabolic parameters in patients with type 2 diabetes mellitus - Atamer, Y.; Atamer, A.; Can, A. S.; Hekimoglu, A.; Ilhan, N.; Yenice, N.; Kocyigit, Y. (Assoc Bras Divulg Cientifica, 2013)
Human serum paraoxonase contributes to the anti-atherogenic effect of high-density lipoprotein cholesterol (HDL-C) and has been shown to protect both low-density lipoprotein cholesterol (LDL-C) and HDL-C against lipid peroxidation. We investigated the effects of rosiglitazone on paraoxonase activity and metabolic parameters in patients with type 2 diabetes mellitus [50 patients (30 males, 20 females); mean +/- SD age: 58.7 +/- 9.2 years, body mass index: 28.2 +/- 4.1 kg/m(2)], in whom glucose control could not be achieved despite treatment with metformin, sulphonylurea, and/or insulin. The patients were given 4 mg/day rosiglitazone for 3 months in addition to their usual treatment. Serum paraoxonase activity, malondialdehyde, homocysteine, and lipid profile were measured at the time of initiation and at the end of therapy with rosiglitazone. After rosiglitazone therapy, serum levels of HDL-C, apolipoprotein A-1, and paraoxonase activity increased significantly (P<0.05) and malondialdehyde, homocysteine, lipoprotein(a), and glucose levels decreased significantly (P<0.05), but no significant changes in levels of total cholesterol and apolipoprotein B were observed. Triglyceride levels also increased significantly (P<0.05). Rosiglitazone treatment led to an improvement in glycemic control and to an increase in paraoxonase activity and HDL-C levels. Although rosiglitazone showed favorable effects on oxidant/antioxidant balance and lipid profile, further studies are needed to determine the effect of rosiglitazone on cardiovascular risk factors and cardiovascular morbidity and mortality.
Keywords: Rosiglitazone; Diabetes mellitus type 2; Paraoxonase; Lipoproteins; Homocysteine; Lipid peroxidation